Negotiating Identity across Borders in Arab Anglophone Diasporic Writings: Reflections on Abbas El-Zein’s Leave to Remain (2008) - Lahcen Ait Idir (LISANIA: Journal of Arabic Education and Literature, 2023)
Generally, diaspora narratives are about leaving and returning. Throughout these processes, diasporas engage in negotiating their identities, inside and outside their country of origin, construct different memories, and exhibit a plethora of feelings and attitudes. In this regard, Abbas El-Zein’s memoir Leave to Remain is preoccupied with a constant search for identity and being in Lebanon and elsewhere. The current paper examines El-Zein’s discourse on belonging through the identification negotiation. It discusses how his multiple identifications as Lebanese, Arab, and Australian are at work through a continuous struggle informed by different attitudes and feelings. El-Zein had “inhabited” and visited many places like America, England, Japan, Paris, Iraq, Australia, etc. This makes him a transnational diasporist, experiencing multi-placedness.